PENERAPAN ALGORITMA BOYER MOORE PADA FUNGSI PENCARIAN DOKUMEN ARSIP BERBASIS WEBSITE (Studi Kasus: Karang Taruna Cipulir RW/005) - Rafly Meidiaz Satria; Romi Andrianto (CV. Multi Kreasi Media, 2024)
The archiving process at Karang Taruna Cipulir RW.05 still uses a manual process, where this manual process can cause problems in the archiving process such as archive buildup and archive loss. The amount of archival data that must be stored from the year must require a special place and require a long time to find old archives. In addition, the absence of a system that manages the archive makes work ineffective and efficient. In order for operational activities to run effectively, a computerized archive system is needed to integrate archives in one unified database, so that records management can be managed properly. In the development of a software, system failures often occur, errors in development are often called software crises which are basically software that is built not in accordance with the goals to be achieved. To avoid this software crisis there are several methods in making software where in this study researchers used the Boyer Moore method. The result of this research is that archive storage is more effective and archive search is more efficient, does not require a long time